Coreid Bug, Leaf-footed Bug, Euthochtha galeator (Fabricius) (Insecta: Hemiptera: Coreidae) - Frank W. Mead (EDIS, 2005)
The coreid bug, Euthochtha galeator (Fabricius), is common throughout the eastern United States west to the Great Plains (Slater and Baranowski 1978). The Florida State Collection of Arthropods (FSCA) contains numerous specimens and reports ranging from the northwestern tip of Florida to Key West. It feeds on a variety of wild and cultivated plants, occasionally becoming a pest primarily in dooryard situations where it can injure roses, citrus, and other fruits and ornamentals. This document is EENY-293 (originally published as DPI Entomology Circular 222), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2003.